Lesa Scholl, Food Restraint and Fasting in Victorian Religion and Literature. : A Book Review - Ghosh, Debasree (SARE: Southeast Asian Review of English, 2023)
Abstract This is an academic review of Lesa Scholl’s groundbreaking work Food Restraint and Fasting in Victorian Religion and Literature (2022), which examines the theological, political and socio-economic motivations which underpin food restraint and fasting in Victorian England. Keywords: y.